MENINGKATKAN KEMAMPUAN MENULIS KARANGAN NARASI MELALUI MODEL CONTEXTUAL TEACHING AND LEARNING PADA SISWA KELAS IV SDN - Viola Novinka Hidayat; Rusmin Husain; Fidyawati Monoarfa; Wiwy Triyanty Pulukadang; Sukri Katili (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research aims to improve narrative writing skills among grade IV students at SDN 2 Kabila, Bone Bolango Regency, through the Contextual Teaching and Learning model. This type of research is Classroom Action Research, conducted in 2 cycles, Data collection techniques included tests, observation, and documentation. The implementation process covered 4 stages: planning, action, observation, and evaluation, analysis, and reflection. The research subjects were 15 grade IV students at SDN 2 Kabila. Observation results showed that of the 15 students, only 3, or 20%, were able to write narrative essays, while 12, or 80%, were unable, In Cyele I, Meeting I, 5 out of 15 students (33%) were capable. In Cycle I, Meeting II. 9 out of 15 students (60%) were capable. In Cycle II, Meeting I, narrative writing skills through the Contextual Teaching and Learning model among grade IV students at SDN 2 Kabila, Bone Bolango Regency, experienced a significant increase, as evidenced by the number of capable students, which reached 14 students (93%). Therefore, it can be concluded that the abilities of grade IV students at SDN 2 Kabila, Bone Bolango Regency, have improved. ABSTRAK Penelitian ini bertujuan untuk meningkatkan kemampuan menulis karangan melalui model Contectual Teaching And Learning pada siswa Kelas IV SDN 2 Kabila Kabupaten Bone Bolango. Jenis Penelitian ini adalah penelitian tindakan kelas, dengan pelaksanaan 2 siklus. Tehnik pengumpulan data tes, observasi, dan dokumentasi. Proses Pelaksanaan mencangkup 4 tahap yaitu perencanaan, tindakan, observasi, evaluasi, analisis dan refleksi. Dengan subjek penelitian adalah siswa kelas IV SDN 2 Kabila yang berjumlah 15 siswa. Hasil observasi menunjukkan kemampuan menulis karangan narasi dari 15 siswa hanya 3 siswa yang mampu menulis karangan narasi atau 20% dan 12 atau 80% siswa tidak mampu. Siklus I pertemuan I dari 15 siswa ada 5 siswa yang mampu atau 33%. Pelaksanaan Siklus I Pertemuan II dari 15 siswa yang mampu 9 atau 60%. Siklus II Pertemuan I kemampuan menulis karangan narasi melalui model Contectual Teaching and Learning pada siswa kelas IV SDN 2 Kabila, Kabupaten Bone Bolango mengalami peningkatan signifikan, dilihat dari jumlah siswa yang mampu menulis karangan narasi sebanyak 14 siswa atau 93%, Jadi dapat disimpulkan kemampuan siswa kelas IV SDN 2 Kabila, Kabupaten Bone Bolango mengalami peningkatan.